Growth Response of Soybean (Glycine max L Merrill) to NPK Fertilizer Dosage and Distance Planting in the Field - Lisdayani; Putri Mustika Sari; Syahman margolang (Jurnal Online Pertanian Tropik, 2021)
In The effort to increase soybean production, various treatments can be applied, one of which is cultivation in which spacing between the plants is adjusted to obtain ideal production. Spacing is determined depending on seed growth, soil fertility, season, and the variety of plants. Apart from spacing, the use of compound fertilizer is also very important in the growth and production of soybean plants. One way to reduce production costs and improve the soil and crop yield quality is applying a compound fertilizer such as NPK Mutiara (16:16:16). NPK (16:16:16) fertilizer has a balanced composition of nutrients and dissolves slowly until the end of the growth process. The purpose of this study is to discover the effect of plant spacing and dosage of NPK Mutiara (16:16:16) fertilizer, and the best interaction between spacing and NPK Mutiara (16:16:16) fertilizer dosage, on the growth and yield of soybean plants (Glycine max (L) Merrill). The research was conducted in a farmer’s experimental garden, in Jalan Eka Suka 11, Pangkalan Mansur Village, Medan Johor District, at a height of ± 15 meters above sea level. The method used is a factorial randomized block design (RBD) with the first factor being plant spacing, and the second -factor being NPK fertilizer dosage. The results of the research show that NPK fertilizer dosage and plant spacing both have a significant effect on plant height and the number of branches. The highest plant height, 75.50 cm, was obtained using the treatment J3 (40 cm x 40 cm spacing), compared with the other two treatments. The lowest plant height, 61.08 cm, was obtained using the treatment J1 (30 cm x 30 cm spacing). The highest number of branches was seen in the treatment K3, with 7.00 stalks, while the lowest number of branches was found in the treatment K0, with 6.03 stalks.